2018
DOI: 10.1186/s13059-018-1464-7
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A and TET1 cooperate to regulate promoter epigenetic landscapes in mouse embryonic stem cells

Abstract: BackgroundDNA methylation is a heritable epigenetic mark, enabling stable but reversible gene repression. In mammalian cells, DNA methyltransferases (DNMTs) are responsible for modifying cytosine to 5-methylcytosine (5mC), which can be further oxidized by the TET dioxygenases to ultimately cause DNA demethylation. However, the genome-wide cooperation and functions of these two families of proteins, especially at large under-methylated regions, called canyons, remain largely unknown.ResultsHere we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 54 publications
9
121
1
Order By: Relevance
“…Previous reports have also shown TET1 and DNMT3A have competitive binding to regulate promoters in mouse embryonic stem cells 83 . In addition, in honey bee Dnmts and Tet (homolog of vertebrate DNMTs and TETs) were found to target memory-associated genes sequentially, while Dnmt3 was found in a negative feedback loop for DNA methylation 84 .…”
Section: Regulatory Loops On Dna Methylationmentioning
confidence: 83%
“…Previous reports have also shown TET1 and DNMT3A have competitive binding to regulate promoters in mouse embryonic stem cells 83 . In addition, in honey bee Dnmts and Tet (homolog of vertebrate DNMTs and TETs) were found to target memory-associated genes sequentially, while Dnmt3 was found in a negative feedback loop for DNA methylation 84 .…”
Section: Regulatory Loops On Dna Methylationmentioning
confidence: 83%
“…Our study showed that temperature stress had no effect on the expression of Tet2 and Tet3. On the other hand, Tet1 was upregulated at 41 C compared to 37 C. We found that both Tet1 and Dnmt3a were highly expressed at 41 C. A recent study reported that DNMT3a and TET1 regulate gene expression not only by controlling DNA methylation but also regulating the histone landscape upon binding to the relevant promoters [38].…”
Section: Discussionmentioning
confidence: 52%
“…We also identify 1,918 genes that show differential isoform use across stage transitions (Figures S3H and S3I; Table S2). These include a switch towards DNMT3A and TET1 isoforms generated from alternative promoters upon endocrine commitment ( Figures 1C, S3J and S3K), which reportedly confer distinct subnuclear localization/biochemical activities (Chen et al, 2002;Gu et al, 2018; Zhang et al, 2016).…”
Section: Epigenome States During Islet Lineage Progressionmentioning
confidence: 99%
“…We also identify 1,918 genes that show differential isoform use across stage transitions (Figures S3H and S3I; Table S2). These include a switch towards DNMT3A and TET1 isoforms generated from alternative promoters upon endocrine commitment ( Figures 1C, S3J and S3K), which reportedly confer distinct subnuclear localization/biochemical activities (Chen et al, 2002;Gu et al, 2018; Zhang et al, 2016).We next used ChIP-seq to profile H3K27ac, which marks active promoters/enhancers, and H3K4me1, which marks either active or poised promoters/enhancers (see below) (Creyghton et al, 2010;Heintzman et al, 2009;Rada-Iglesias et al, 2011), and identified 361,576 sites enriched for H3K27ac/H3K4me1 in at least one stage. Despite consistent genomic coverage and histone modification levels during differentiation ( Figure S2A, S4A-S4C), >75% of H3K27ac/ H3K4me1 regions are detected in at most 3 stages ( Figure S4D).…”
mentioning
confidence: 99%